Neoproterozoic hydrothermal activity in the West Australian Craton related to Rodinia assembly or breakup? - Olierook, Hugo; Agangi, Andrea; Plavsa, Diana; Reddy, Steven; Yao, Weihua; Clark, Christopher; Occhipinti, S.; Kylander-Clark, A. (Elsevier BV, 2019)
The timing of final assembly and initiation of subsequent rifting of Rodinia is disputed. New rutile ages (913 ± 9 Ma, 900 ± 8 Ma and 873 ± 3 Ma) and published zircon, monazite, titanite, biotite, muscovite and xenotime geochronology from the Capricorn Orogen (West Australian Craton) reveal a significant early Neoproterozoic event characterized by very low to low metamorphic grade, abundant metasomatism, minor leucogranitic and pegmatitic magmatism and NW–SE fault reactivation episodes between ca. 955 and 830 Ma. Collectively, these are termed the ca. 955–830 Ma Kuparr Tectonic Event. An age range of ca. 955–830 Ma is concomitant with the final stages of Rodinia assembly and the initial stages of its attempted breakup. Very low- to low-grade metamorphic and structural geological evidence favor a distal north–south compressional regime as the driver for hydrothermal activity during ca. 955–830 Ma. Nearby continental collision or accretion from the west (e.g., South China and/or Tarim) are ruled out. The cessation of metasomatism and magmatism in the West Australian Craton after ca. 830 Ma is concomitant with the emplacement of the Gairdner–Amata dyke swarm and associated magmatic activity in South China and Laurentia, the inception of the Adelaide Rift Complex and the deposition of the Centralian Superbasin. We posit that the cessation of hydrothermal activity in the Capricorn Orogen was caused by a tectonic switch from compressional to extensional at ca. 830 Ma. Magmatic and hydrothermal fluids were transferred away from the Capricorn Orogen to the incipient Adelaide Rift Complex, terminating metasomatism in the West Australian Craton. Ultimately, the Kuparr Tectonic Event marked the final stages of Rodinia assembly and its cessation marks the initial stages of its attempted breakup.